The socio-economics of pandemics policy - Dennis J. Snower (Institute of Labor Economics (IZA), 2020)
In response to the Covid-19 pandemic, governments around the world have provided a massive fiscal and monetary stimulus. While this policy is welcome in the short run, it does not address the underlying problem in the medium and long run. The reason is that the pandemic has not given rise to a generalized shortfall in aggregate demand. Rather, it has generated a Great Economic Mismatch, characterized by deficient demand for things requiring close physical interactions among people and deficient supply of things compatible with social distancing, where appropriate. Expansive macroeconomic policy can stimulate aggregate demand, but when social distancing is enforced, it will not stimulate production and consumption whenever this demand is satisfied through physically interactive activities. To overcome the Great Economic Mismatch, "readaptation policies" are called for. In the medium run, these policies promote a redirection of resources to activities compatible with social distancing; the long run, these policies make economies more resilient to unforeseen shocks that generate a Great Economic Mismatch. Once the pandemic is over, a more profound rethinking of decision making - in public policy, business and civil society - is called for. First, decision makers will need to supplement the current focus on economic efficiency by greater emphasis on economic resilience. Second, economic policies and business strategies will need to focus less on incentives for selfish individuals and more on the mobilization of people's prosocial motives. Finally, to encourage people around the world to cooperate globally in tackling global problems, policy makers at local, national and global levels will need to encourage people around the world to cooperate globally in tackling global problems, with the aid of two powerful tools that humans throughout history have used to coordinate their efforts: identity-shaping narratives and institutions of multi-level governance.
Keywords: E61; H12; J2; 330; COVID-19; pandemics policy; macroeconomic policy; economic mismatch; economic resilience